Community-level epidemiology of soil-transmitted helminths in the context of school-based deworming: Baseline results of a cluster randomised trial on the coast of Kenya. - Katherine E Halliday; William E Oswald; Carlos Mcharo; Emma Beaumont; Paul M Gichuki; Stella Kepha; Stefan S Witek-McManus; Sultani H Matendechero; Hajara El-Busaidy; Redempta Muendo; Athuman N Chiguzo; Jorge Cano; et al. (Public Library of Science (PLoS), 2019)
Trial registration ClinicalTrials.gov NCT02397772.